1988
DOI: 10.1530/jrf.0.0820657
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of alkaline phosphatase from boar seminal plasma

Abstract: An alkaline phosphatase was purified from boar seminal plasma using adsorption to calcium phosphate gel, gel filtration, and ion-exchange chromatography. The preparation gave a single band on SDS polyacrylamide electrophoresis. The enzyme was a non-specific alkaline phosphatase that hydrolysed pyrophosphate slowly and had no phosphodiesterase activity. The pH optimum was 10 and the Km was approximately 0.2 mM with p-nitrophenyl phosphate as substrate. The enzyme was a zinc metalloenzyme as indicated by the los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…To better characterize the plasma enzyme, AP thermoinhibition was carried out at 60 °C, as described by Iyer et al . () with some modifications: the samples were kept at 60 °C for 1′15″, 2′30″, 5′, 10′, then placed in ice and the activity was measured within 30″. The same assay was also performed on the thermostable AP from bovine intestinal mucosa as a control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better characterize the plasma enzyme, AP thermoinhibition was carried out at 60 °C, as described by Iyer et al . () with some modifications: the samples were kept at 60 °C for 1′15″, 2′30″, 5′, 10′, then placed in ice and the activity was measured within 30″. The same assay was also performed on the thermostable AP from bovine intestinal mucosa as a control.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Iyer et al . () reported that two isoforms of AP seem to be present in boar seminal plasma.…”
Section: Introductionmentioning
confidence: 98%
“…. , , _.. 1/4 ^ τ · j-' · ι η -j t. Λ The present investigation was concerned with the disammals (1)(2)(3)(4)(5)(6). It is secreted into seminal fluid by the ., .…”
mentioning
confidence: 99%
“…. ,,., j j " , c r\ Λ u +u * * tnbution of alkaline phosphatase activity in split ejacepididymis in rabbit and dog (5,6) and by the prostate , r , V ^i-ni-, 4 V "· /< o\ χ* Τ ι u-i * u · ulates of human semen, the response of this alkaline and testis in man (1,3 …”
mentioning
confidence: 99%
“…Alkaline phosphatase is present in both seminal plasma and spermatozoa. In seminal plasma, it is present in multiple forms that share similar kinetic properties, and it generally originates from epididymal fluid (Strzezek and Glogowski, 1979;Glogowski and Strzezek, 1980;Frenette et al, 1986;Glogowski, 1988;Iyer et al, 1988;Tang, 1998). Alkaline phosphatase is present in prostasomes (Fabiani and Ronquist, 1995) and is a component of sperm plasma membranes (Soucek and Vary, 1984;Parks et al, 1987).…”
Section: Discussionmentioning
confidence: 99%